1984
DOI: 10.1007/bf01321323
|View full text |Cite
|
Sign up to set email alerts
|

Issues in diagnosing anxiety disorders

Abstract: Research progress in the anxiety disorders is predicated on a useful classification system. In this paper, we review the reliability and validity data for the Diagnostic and Statistical Manual of Mental Disorders, anxiety disorders and discuss the salient issues associated with both the conceptualization of anxiety disorders and the diagnostic criteria offered in the DSM-III. It is concluded that the diagnostic reliability for these disorders is, overall, satisfactory. A dearth of validity data, however, hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 64 publications
3
7
0
Order By: Relevance
“…It was also reported in an earlier study by Turner, McCann, Beidel, & Mezzich (1986) that socially phobic subjects experience considerably more general anxiety and depression than do those individuals with simple phobia, but somewhat less than the anxiety states. Similar findings were reported by Cerny et al (1984).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was also reported in an earlier study by Turner, McCann, Beidel, & Mezzich (1986) that socially phobic subjects experience considerably more general anxiety and depression than do those individuals with simple phobia, but somewhat less than the anxiety states. Similar findings were reported by Cerny et al (1984).…”
Section: Discussionsupporting
confidence: 92%
“…Although we have witnessed an explosion in the quantity and type of research in the anxiety disorders over the past few years, one anxiety disorder, social phobia, remains relatively unstudied. Socially phobic behavior can be seen in a number of clinical syndromes (Cerny, Himadi, & Barlow, 1984), but socially phobic individuals meeting DSM-III criteria are specifically characterized by fear of negative evaluation and scrutiny by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(DSM-III;American Psychiatric Association, 1980)] has clearly improved the precision in the classification of psychiatric disturbances including the anxiety disorders. This system is far from perfect, which is attested to by the current work being undertaken on a revision (DSM-III-R) in which some changes will be made in at least one anxiety category-generalized anxiety disorder (see Cerny, Himadi, & Barlow, 1984). Thus, the architects of the DSM-III, as well as its many critics, recognize that there are limitations to the current system.…”
Section: Symptom Overlap In the Anxiety Disordersmentioning
confidence: 86%
“…The classification of agoraphobia within the Diagnostic and Statistical Manual (DSM) for Mental Disorders has undergone significant changes over time and continues to be a controversial issue [Cerny et al, 1984]. Marks and Bebbington [1976] originally suggested that agoraphobia was a phobic disorder arising from fears of public places that may or may not occur with panic attacks.…”
Section: Introductionmentioning
confidence: 99%